2022
DOI: 10.1002/cjs.11743
|View full text |Cite
|
Sign up to set email alerts
|

Canadian contributions to environmetrics

Abstract: This article focuses on the importance of collaboration in statistics by Canadian researchers and highlights the contributions that Canadian statisticians have made to many research areas in environmetrics. We provide a discussion about different vehicles that have been developed for collaboration by Canadians in the environmetrics context as well as specific scientific areas that are focused on environmetrics research in Canada including climate science, forestry, and fisheries, which are areas of importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 167 publications
0
1
0
Order By: Relevance
“…Geostatistical models refer to models applied over point referenced data (Diggle et al, 1998), while preferential models refer to models that account for the dependence between the process under study and the sampling locations (Diggle et al, 2010). Different studies have demonstrated the importance of accounting for the sampling process to infer good abundance estimates (Pennino et al, 2019;Watson et al, 2019;Dean et al, 2022). But, what if we have both randomly and preferentially sampled data?…”
mentioning
confidence: 99%
“…Geostatistical models refer to models applied over point referenced data (Diggle et al, 1998), while preferential models refer to models that account for the dependence between the process under study and the sampling locations (Diggle et al, 2010). Different studies have demonstrated the importance of accounting for the sampling process to infer good abundance estimates (Pennino et al, 2019;Watson et al, 2019;Dean et al, 2022). But, what if we have both randomly and preferentially sampled data?…”
mentioning
confidence: 99%